Dr. Aden Aw Hassan (ICARDA) How climate change impacts farmer incomes in Central Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Aden Aw Hassan of ICARDA shares his research on modeling climate change impacts for Central Asian farmers. https://ccafs.cgiar.org/blog/central-asia-climate-change-makes-or-breaks-farmers-fortunes Research presented at the Global Science Conference on Climate Smart Agriculture, University of California, Davis. 20-22 March 2013.